Genetic variation and diversity in 199 Melilotus accessions based on a combination of 5 DNA sequences - Zhang, Hongxiang; Wu, Fan; Guo, Wenli; Bai, Rong; Yan, Zhuanzhuan; Muvunyi, Blaise Pascal; Yan, Qi; Zhang, Yufei; Yi, Xianfeng; Zhang, Jiyu (PLOS ONE, 2018)
Melilotus is an important genus of legume plants and an herbage with excellent nitrogen fixation; it can tolerate extreme environmental conditions and possesses important medicinal value. However, there is limited genetic information about the genus; thus, we analysed four chloroplast loci (rbcL, matK, psbA-trnH and trnL-F) and one nuclear region (ITS) to determine the genetic diversity of 199 accessions from 18 Melilotus species. The rbcL and matK sequences were highly conserved, whereas the trnL-F and ITS sequences contained variable and parsimony-informative sites. In our analyses of the single and combined regions, we calculated the pairwise distance, haplotype and nucleotide diversity and gaps and then constructed phylogenetic trees to assess the genetic diversity, and our results revealed significant variations among the different accessions. The genetic distance values were between zero and nine, and based on the combined regions, the highest frequency value was approximately four. Melilotus showed high haplotype and nucleotide diversity, particularly in the ITS sequences, with values of 0.86 and 0.0087, respectively. The single ITS sequence, psbA-trnH, and the combined matK+rbcL+trnL-F (MRT) and matK+rbcL+psbA-trnH+trnL-F+ITS (MRPTI) regions showed interspecific variation in the gap analysis. Phylogenetic trees calculated using ITS, psbA-trnH and MRPTI sequences indicated distinct genetic relationship in 18 species, and these species could be divided into two groups. By determining the genetic diversity of plants, we can evaluate the genetic relationships among species and accessions, providing a basis for preserving and utilizing the genetic resources of Melilotus.